A Novel Subtype of Spondylocostal Dysplasia Associated With a Heterozygous Missense FLNA Variant - Haoyu Cai; Xu'an Huang; Haojie Chen; Junduo Zhao; Heng Sun; Yizhen Huang; Jiayue Guo; Jianxiong Shen (Orthopaedic Surgery)
ABSTRACT Background Spondylocostal dysplasia (SCD) is characterized by vertebral defects and rib abnormalities. Following radiological diagnosis, further genetic testing is conducted to confirm the mutant loci and identify the subtype of SCD. While seven loci potentially associated with SCD have been identified, rare cases remain unexplained. Case Presentations A 37‐year‐old female diagnosed with SCD at birth was reported in this study. She exhibited scoliosis and thoracic asymmetry, along with a left‐sided bilateral breast deformity. Imaging analysis revealed congenital scoliosis with a lack of segmentation, deformity of multiple ribs, and a lower spinal cord. Using whole‐exome sequencing, we identified the genetic variant in the afflicted individual. We detected a heterozygous exon 16 FLNA variant in the afflicted individual and confirmed the absence of pathogenic variants of other known SCD‐associated genes. Conclusions The variant NM_001456.4: c.2351T>C detected in this study enhances our knowledge of the pleiotropy linked with heterozygous FLNA variants. By expanding the mutation spectrum of FLNA, these findings will lay a foundation for further studies on the correlation between genotypes and phenotypes.